Albumin-bioinspired iridium oxide nanoplatform with high photothermal conversion efficiency for synergistic chemo-photothermal of osteosarcoma - Wenguang Gu; Tao Zhang; Junsheng Gao; Yi Wang; Dejian Li; Ziwen Zhao; Bo Jiang; Zhiwei Dong; Hui Liu (Taylor & Francis Group, 2019)
Protein-based nanocarriers with inherent biocompatibility have been widely served as building blocks to construct versatile therapeutic nanoplatforms. Herein, bovine serum albumin-iridium oxide nanoparticles (denoted BSA-IrO2 NPs) are successfully synthesized via one-step biomineralization approach. The BSA-IrO2 NPs exhibits uniform size (40 nm), superb biocompatibility and high drug loading capacity for doxorubicin (27.4 wt%). Under near-infrared (NIR) laser irradiation, the as-prepared BSA-IrO2 NPs exhibited high photothermal conversion ability (54.3%) and good photostability. The in vitro drug release experiments displayed pH and NIR laser -triggered DOX release profiles, which could enhance the therapeutic anticancer effect. By utilizing this DOX loaded nanoplatform, effective synergistic chemo-photothermal therapy against human osteosarcoma can be realized, which has been systematically verified both in vitro and in vivo. Notably, in vivo pharmacokinetics studies showed that BSA-IrO2@DOX had prolonged blood circulation time due to the BSA component can improve the stealthiness of the nanoparticles during the blood circulation. Meanwhile, in vitro and in vivo toxicity studies demonstrated that the BSA-IrO2 NPs can act as biocompatible agents for drug delivery and cancer therapy. Therefore, this work presents a biomineralized iridium-based NPs with remarkable features and be used as a very potential therapeutic nanoplatform for cancer treatment.